A Case Report of College Students' Rating of a Shared Decision-Making Tool for Taking Antidepression Medication. (13th April 2021) - Reis, Janet
Forty-nine students enrolled at a medium size public university volunteered to review an interactive decision-making tool constructed to present the pros and cons of taking antidepression medication. The tool is built according to guidelines for shared decision-making with 7 educational sections followed by 4 queries on expectations about antidepressants, 3 key knowledge questions, and determination of readiness to take action. The most frequently cited reason for the content being helpful was improved understanding (78%) followed by increased personal confidence (37%) and helped me take action (14%). The most frequently cited reason for the content not being more helpful was already known information (74%) followed by not enough information (12%). The range of personal preferences underscores the complexity of motivations in responding to depressive symptoms. The prevalence of depression in the college population with a range of treatment options, limitations on resources, and new challenges mounted with the pandemic for campus life recommends further study of such tools.